2013
DOI: 10.2147/amep.s47145
|View full text |Cite
|
Sign up to set email alerts
|

The availability of teaching–pedagogical resources used for promotion of learning in teaching human anatomy

Abstract: Five hundred students attending higher education institutions in northeastern Brazil responded to questionnaires about their anatomy classes; students represented a variety of different health sciences disciplines. Analysis of the responses revealed the participation of teaching assistants in a large percentage of classes and the use of teaching resources, particularly images, from conventional radiographs to magnetic resonance images. The number of classes for cadaver dissection and the number of students wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
(12 reference statements)
0
7
0
1
Order By: Relevance
“…The findings from these studies suggest that dissection allows students to be close to the reality and that dissection performed in anatomy classes is an important tool for the implementation of education within the post‐mortem paradigm. Moreover, majority of the students were of the opinion that dissection makes learning more dynamic and close to the practical context (Aragão et al, ). Further, it contributes to increasing the confidence of the students by reflecting on their self‐learning abilities towards imbibing anatomical knowledge (Rizzolo and Stewart, ).…”
Section: Current Scenario Of Dissection Based Anatomy Teaching In Devmentioning
confidence: 99%
“…The findings from these studies suggest that dissection allows students to be close to the reality and that dissection performed in anatomy classes is an important tool for the implementation of education within the post‐mortem paradigm. Moreover, majority of the students were of the opinion that dissection makes learning more dynamic and close to the practical context (Aragão et al, ). Further, it contributes to increasing the confidence of the students by reflecting on their self‐learning abilities towards imbibing anatomical knowledge (Rizzolo and Stewart, ).…”
Section: Current Scenario Of Dissection Based Anatomy Teaching In Devmentioning
confidence: 99%
“…The benefits in initiating the training of teaching skills at the undergraduate level have positive outcomes in the careers of teaching assistants, as demonstrated by Lachman et al () with medical students. A recent study performed by Brazilian colleagues also reported that the participation of teaching assistants in practical classes of anatomy was a common and effective resource used to improve the teaching/learning process (Aragão et al, ). In agreement with the present study, Hughes () showed that in a peer‐assisted learning program implemented in Anatomy and Physiology (Biology course), students who attended five or more peer‐leader sessions (out of thirty) had significantly higher final grades.…”
Section: Faculty Considerationsmentioning
confidence: 99%
“…The efficacy of peer mentoring programs in university health courses is well‐established (Frei et al, ; Aragão et al, ) and has been employed in universities worldwide (Frei et al, ; Meinel et al, ; Hryciw et al, ). However, there is an increasing demand for universities to integrate different areas of knowledge and to encourage students to participate in an interprofessional learning experience (Buss, ; Thistlethwaite et al, ; Thistlethwaite, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, practical classes involving dissection are not always mandatory in human anatomy courses, and the decision to include them is made by each educational institution (Aragão et al, ). However, there is no published national data on the use of cadavers by universities, but merely isolated reports from some universities in some of the states in the federation (Melo and Pinheiro, ; Aragão et al, ; Da Rocha et al, ; Biasutto et al, ; De Oliveira et al, ).…”
Section: Introductionmentioning
confidence: 99%